Sanksi terhadap Lembaga Peradilan Internasional sebagai Bentuk Obstruction of Justice dalam Perspektif Hukum Pidana Internasional - Nabila Inkha Putri; Dwi Putri Lestarika (AHKAM, 2026)
The increasing practice of unilateral sanctions imposed by states against the International Criminal Court (ICC) has the potential to disrupt the independence and effectiveness of international judicial institutions. From the perspective of international criminal law, such actions raise serious issues because they may be qualified as obstruction of justice, namely acts that impede judicial proceedings. This study aims to analyze whether sanctions against the ICC can be qualified as obstruction of justice and to examine the mechanisms of legal accountability for such actions within the framework of international law. This study used a normative legal method with a statute approach and a conceptual approach. The legal materials used included the 1998 Rome Statute, the United Nations Convention Against Corruption (UNCAC), and various relevant international legal literature. The results showed that the concept of obstruction of justice in international criminal law has been regulated through provisions that criminalize acts interfering with the administration of justice. Sanctions against the ICC meet the three elements of obstruction of justice, namely causing delays in legal proceedings by paralyzing court operations, being carried out with full knowledge of the impact of such actions, and aiming to interfere with the administration of justice to protect citizens from criminal accountability. This action violates the principle of judicial independence, creates impunity, and leaves victims without access to justice. Thus, this study emphasizes the importance of strengthening protection for international justice through the activation of blocking statutes and the solidarity of States Parties in order to safeguard the independence, effectiveness, and legitimacy of the International Criminal Court.